A proteção das pessoas com deficiência por meio das ações afirmativas no direito tributário - Jesus, Alessandra Pinheiro Rodrigues D'Aquino de (2016)
The core of this research is the study of affirmative actions in tax law aimed at protecting the person with disability. It seeks to answer the following questions: are there relevant and injustified inequalities on the treatment given to disabled persons? Is the elimination of these inequalities conformed to the values laid down in the Brazilian Constitution? Is the tax law a field of law that should be used as a tool for the elimination of existing barriers aimed at concretion of objectives and constitutional values? Which mechanisms does the tax law have to achieve these goals? Are the measures taken achieving the desired goals? The choice of theme is justified by the importance of the real implementation of actions that allow the person with disability to have effective participation in society on equal basis with others. The hypothesis that guided the research is that the tax law has not denied these needs and has relevant mechanisms to mitigate the various barriers that obstruct the full exercise of the right to life with dignity, locomotion, communication, education and work by persons with disabilities. At first, the research consisted in the analysis of law, from the perspective of fact, value and rule, at which various institutes were considered in the relevant points for understanding the protection of disabled persons. Secondly, it was conducted a general analysis of the various rights guaranteed to persons with disabilities by the Brazilian Constitution, the United Nations Convention on the Rights of Persons with Disabilities and the Statute of Persons with Disabilities and, also, it was justified the adoption of affirmative actions to the protection of these persons. Finally, a deep research into affirmative actions in tax law was conducted, during which was established the correspondence between affirmative actions and the granting of tax benefits for the protection of the person with disability and the various benefits existing in the Brazilian legal system were exposed. It was noted the importance of granting tax benefits for the protection of people with disabilities, although it is possible go further to significant results